Controlled release of dexamethasone sodium phosphate with biodegradable nanoparticles for preventing experimental corneal neovascularization - Wang, Bing (Nanomedicine, 2019)
Corneal neovascularization (CNV) leads to the loss of corneal transparency and vision impairment, and can ultimately cause blindness. Topical corticosteroids are the first line treatment for suppressing CNV, but poor ocular bioavailability and rapid clearance of eye drops makes frequent administration necessary. Patient compliance with frequent eye drop regimens is poor. We developed biodegradable nanoparticles loaded with dexamethasone sodium phosphate (DSP) using zinc ion bridging, DSP-Zn-NP, with dense coatings of poly(ethylene glycol) (PEG). DSP-Zn-NP were safe and capable of providing sustained delivery of DSP to the front of the eye following subconjunctival (SCT) administration in rats. We reported that a single SCT administration of DSP-Zn-NP prevented suture-induced CNV in rats for two weeks. In contrast, the eyes receiving SCT administration of either saline or DSP solution developed extensive CNV in less than 1 week. SCT administration of DSP-Zn-NP could be an effective strategy in preventing and treating CNV.